3D Printing - Dawn of a New Era in Learning Veterinary Anatomy - Sivagnanam, (Indian Journal of Veterinary Anatomy, 2022)
Veterinary Anatomy is a discipline concerned with teaching and learning of three-dimensionalstructures of animal body. The Veterinary anatomy has historically been the cornerstone of all the disciplines ofhuman medicine, veterinary and animal sciences. Traditional anatomy teaching methods consist of didacticlecture with chalk and talk, PPT presentations, prosection by teacher and dissection by student. This study is toreveal the current technology of teaching and learning by making 3D Anatomical specimens which would helpboth faculty and students to get rid of Carcinogenic formalin vapour both in the laboratories and museums. Anovel method of CT scanning and creation of DICOM files for producing Raw rasterized data is found in thisresearch. Also the obtained data are converted to STL (Standard Tessellation Language) files that are readilyprintable in any 3D Printer. ACanine humerus is printed using the new technology to demonstrate that all anatomyteaching models could be produced without quality compromise in future using FDM and SLA type of 3DPrinters.Healthy living is the right of every human. In this context 3D printed learning aids are boon in pedagogy.The materials, methods and advantages of 3D prints of biological specimens over other techniques of VeterinaryAnatomy teaching are discussed in this research.Adopting the 3D printing technology in making VeterinaryAnatomy specimens is certainly a dawn of new era in learning Veterinary Anatomy.